2015
DOI: 10.1177/1475921715599050
|View full text |Cite
|
Sign up to set email alerts
|

An improved fractal prediction model for forecasting mine slope deformation using GM (1, 1)

Abstract: The forecasting slope deformation potential is required to evaluate slope safety during open-pit mining, allowing us to formulate and promote effective emergency strategies in advance to prevent slope failure disasters. Although fractal models have been used to predict slope deformation, such limitations as low prediction accuracy, poor stability and the requirement for large amounts of data must be overcome. This article proposes an improved fractal model to forecast mine slope deformation using the grey syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The number of hidden layers of the ELM model is 6 and the transfer function is sig type through the trial algorithm, and the prediction result of ELM is obtained, and compared with the BP (Sun, 2014;Xie, et al, 2014) and GM (1,1) (Sun, 2014;Sun et al, 2016;Wu, et al, 2015) models, as shown in Figure 2. Analysis of Figure 2 shows that the prediction results of the BP model can predict the trend of displacement, but almost every predicted value deviates from the real value, and the prediction result is the worst; the prediction effect of the GM (1,1) model is better than that of the BP model, but the model predicts Unstable, the predictive effect is also poor.…”
Section: Deformation Prediction and Results Analysismentioning
confidence: 99%
“…The number of hidden layers of the ELM model is 6 and the transfer function is sig type through the trial algorithm, and the prediction result of ELM is obtained, and compared with the BP (Sun, 2014;Xie, et al, 2014) and GM (1,1) (Sun, 2014;Sun et al, 2016;Wu, et al, 2015) models, as shown in Figure 2. Analysis of Figure 2 shows that the prediction results of the BP model can predict the trend of displacement, but almost every predicted value deviates from the real value, and the prediction result is the worst; the prediction effect of the GM (1,1) model is better than that of the BP model, but the model predicts Unstable, the predictive effect is also poor.…”
Section: Deformation Prediction and Results Analysismentioning
confidence: 99%
“…However, it poses a challenge in the practical application of prediction when facing the uncertainty and non-stationary features inherent in the monitoring data. To solve this aspect, different forecasting algorithms have been widely studied and attempted, for instance, the statistical models, 6 time series models, 7 gray system theory, 8 and singular spectrum model. 9 More recently, the Bayesian forecasting model has been applied in real-world data prediction due to its merits.…”
Section: Introductionmentioning
confidence: 99%
“…e GM (1, 1) model can extract the chaotic data series. Trends, generate new data columns and use them for predictive analysis [13]. Foundation pit deformation is a complex and nonlinear problem.…”
Section: Introductionmentioning
confidence: 99%